MULTILUMEN CATHETER - SHAH, RAJIV; GIRON, VICTOR; GOTTLIEB, REBECCA; MORRIS, MARY M; MILLER, MICHAEL E; ENEGREN, BRADLEY J (2012)
A multilumen catheter (10) having tubings (16, 18, 22) extending into lumens within the catheter (10). The lumens may be used for blood, drugs or other medicants. The lumens may also be used for sensors. The junction element (14), external to the patient, connects the tubings (16, 18, 22). The tubings (16, 18, 22), also external to the patient, connect to infusion members (26), to which one or more infusion systems may be connected to deliver blood, drugs and other medicants to the patient. A sensor (22) having a sensing element (24) may extend through the sensor lumen and be positioned internal to the patient for physiological parameter sensing. An external portion of the sensor (2) may be connected to associated electronics to provide automatic monitoring of the physiological parameters and automatic delivery and control of the infusants. Also, a central line catheter (100) for delivering fluids directly into a main artery or vein near the heart, which contains a first lumen (106) to deliver a fluid through the central line catheter (100) and a second lumen (110) containing a sensor capable indicating a characteristic level in blood. In addition, the central line catheter (100) can further include a flush sleeve to remove debris around the sensor.